HIV, HSV, SARS-CoV-2 and Ebola Share Long-Term Neuropsychiatric Sequelae - Büttiker, Pascal; Stefano, George B; Weissenberger, Simon; Ptacek, Radek; Anders, Martin; Raboch, Jiri; Kream, Richard M (Neuropsychiatric disease and treatment, 2022)
Long COVID, in which disease-related symptoms persist for months after recovery, has led to a revival of the discussion of whether neuropsychiatric long-term symptoms after viral infections indeed result from virulent activity or are purely psychological phenomena. In this review, we demonstrate that, despite showing differences in structure and targeting, many viruses have highly similar neuropsychiatric effects on the host. Herein, we compare severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), human immunodeficiency virus 1 (HIV-1), Ebola virus disease (EVD), and herpes simplex virus 1 (HSV-1). We provide evidence that the mutual symptoms of acute and long-term anxiety, depression and post-traumatic stress among these viral infections are likely to result from primary viral activity, thus suggesting that these viruses share neuroinvasive strategies in common. Moreover, it appears that secondary induced environmental stress can lead to the emergence of psychopathologies and increased susceptibility to viral (re)infection in infected individuals. We hypothesize that a positive feedback loop of virus-environment-reinforced systemic responses exists. It is surmised that this cycle of primary virulent activity and secondary stress-induced reactivation, may be detrimental to infected individuals by maintaining and reinforcing the host's immunocompromised state of chronic inflammation, immunological strain, and maladaptive central-nervous-system activity. We propose that this state can lead to perturbed cognitive processing and promote aversive learning, which may manifest as acute, long-term neuropsychiatric illness.
Keywords: virus latency; HIV-1; interoception; neuropsychiatry; SARS virus